(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Creativity and socio-economic status both are the significant factors identified with every single identity living in a specific culture. The present examination was an undertaking to discover the Creativity and Socio-Economic Status of Secondary School Students.